(untitled) (Economics and region, 2019)
Financial inclusion of the region is a means of making full use of the financial services industry’s tools, which ultimately contributes to the long-term economic growth of the region, as it stimulates innovation, mobilizes savings and supports investment. The paper analyzes the current level of financial inclusion of the Poltava region. The study showed that the current level of financial inclusion of the Poltava region is low. Surveys of the respondents showed that there is a large disproportionate level of financial inclusion among urban and rural population. The rural population is limited in financial services. There is still a significant lack of confidence in financial institutions. All this slows down the processes of full involvement of the population in financial inclusion and creates a shadow sector. However, remediation is observed in urgent action by both the state and local authorities and financial institutions. Continuous information in the media and social networks in the future will be able to restore confidence in financial institutions and thus increase not only the level of financial inclusion, but also every inhabitant of the Poltava region.